Poets of Protest : Mythological Resignification in American Antebellum and German Vorm?arz Literature. - Michael Rodegang Drescher (American Culture Studies, 2016)
Michael Drescher analyzes national mythologies in American and German literature. He focuses on processes of mythological resignification, a literary phenomenon carrying significant implications for questions of identity, democracy, and nationalism in Europe and America. Precise narratological analyses are paired with detailed, transnational readings of Hawthorne's The Scarlet Letter, Gutzkow's Wally, die Zweiflerin, Brown's Clotel, and Heine's Deutschland. Ein Wintermärchen. The study marries literature, mythology, and politics and contributes to the study of American and German literature at large.